The Implementation of Islamic Spiritual Values in Entrepreneurship at PLUT KUMKM Partners in Yogyakarta - Tazkiyah Ainul Qolbi; Salmia Salmia; Teguh Adimarta (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Objective: Penelitian ini bertujuan untuk mengetahui implementasi nilai-nilai spiritual Islam dalam berwirausaha pada Mitra PLUT KUMKM DIY Design/Method/ approach: This study uses a qualitative method, a naturalistic research with a phenomenological approach. The data used are primary data collected through direct interviews. Determining the sources using purposive sampling technique. The interview guidelines used were semi-structured interviews. Data analysis techniques, namely the stage of data reduction, data presentation and conclusions. This method is used in order to determine the implementation of Islamic spiritual values in entrepreneurship in PLUT KUMKM Partners in the Special Region of Yogyakarta.Findings: The results of this studynamely first doing business to seek the pleasure of Allah SWT, Partners of PLUT KUMKM DIY have implemented this, entrepreneurship for worship and become a way of sustenance. Second, think positively, Partners of PLUT KUMKM DIY have a positive way of thinking in dealing with entrepreneurial failures. Third, oriented to the afterlife, Mitra PLUT KUMKM DIY tries to be afterward-oriented in entrepreneurship. Fourth, charity ma'ruf nahi munkar, in this case the implementation of PLUT KUMKM Partners is still lacking because they prefer to remain silent if there is no direct relationship with him.Originality/Value: This research is expected to providean illustration for PLUT KUMKM DIY in determining the direction of MSME assistance policies by applying Islamic spirituality values in entrepreneurship.